Paraspara, Encounters, and Confluences: India's Soft Power Objective in the Indo‐Pacific Region. Issue 5 (26th October 2017) - Singh, Amit; Sarwal, Amit
Abstract : The ties between India and the countries in the Indo‐Pacific region go back to the pre‐Christian era. Even today, Indian influence on the language, customs, and rituals is visible in Southeast Asia. The Hindu concepts of kingship, administrative institutions, and ceremonies that became deeply embedded in the royal culture of Southeast Asia were disrupted with the arrival of the colonial powers. These traditional linkages have become the key element of India's diplomacy—the "Look East" and the "Act East" policies. This article studies the background of India's sustained public and cultural diplomacy policy in bridging the gap between India, East Asia, and the Indo‐Pacific countries in the context of the Act East policy. Using examples from Modi's yoga diplomacy, Bollywood, and Indian cultural festivals, the authors propose that these initiatives should be seen as part of a historical and traditional concept of " paraspara "—mutually sustainable and reciprocal diplomacy that taps into the opportunities in the Indo‐Pacific region.